Penerapan Metode Six Sigma untuk Menurunkan Terjadinya Keterlambatan Informasi Kedatangan Barang (NOA) dalam Kegiatan Impor - Firmansyah, Iqbal; Poncotoyo, Wahyu; Maulana, Andy; Zain, Abdul Razaq; Ferdiansyah, Anton; Lestari, Sinta Ayu (Jurnal Sistem Transportasi & Logistik, 2021)
The purpose of this study was to find out and obtain an in-depth description and understanding of the problems that cause delays in the arrival of imported goods (NoA) via air cargo, as a company engaged in cargo and warehouse rental PT Jasa Angkasa Semesta provides the best service in carrying out import activities. , as well as loading and unloading activities, document preparation, and communication between shippers. The research method in writing this thesis is to take certain objects to be analyzed and understood by focusing on a problem. By using the Six Sigma method, it is hoped that it will be possible to make improvements and improvements as well as continuous improvements to the problems studied.